Eruptive Necrotizing Infundibular Crystalline Folliculitis: An Expression of an Abortive Sebaceous Follicular Repair Pathway Linked to Committed Infundibular Stem Cells?. (December 2021) - Kossard, Steven
Abstract : Abstract: Necrotizing infundibular crystalline folliculitis is a rare entity, which is a distinctive clinical and histopathological entity. Eruptive yellow waxy umbilicated folliculocentric plugs clinically correspond to pale crystalline filaments embedded in an amorphous sebum-rich material. Remarkably, only the superficial infundibular ostia remain, and the distended cavity is devoid of a follicular or sebaceous gland remnant. The pathogenesis of this enigmatic event remains to be established. The emergence of necrotizing infundibular crystalline folliculitis (NICF) as a paradoxical side effect of antitumor inhibitors epidermal growth factor receptor vascular endothelial growth factor and more recently programmed death-1 represents the expression of altered molecular pathways that underpin the pathogenesis of NICF. To explore these pathways, it is necessary to explore the hierarchy of follicular stem cells, particularly the potential role of committed infundibular stem cells that play a key role in wound healing. Committed infundibular stem cells are closely linked to the sebaceous gland stem cell axis, and this has relevance in the process of homeostatic repair of sebaceous follicles in the wake of folliculitis. The unscheduled modulation of this infundibular homeostatic sebaceous repair axis by epidermal growth factor receptor vascular endothelial growth factor, and programmed death-1 may lead to an aberrant outcome with metaplasia of infundibular keratinocytes to sebocytes. In the absence of sebaceous gland differentiation, these metaplastic infundibular sebocyte cells would lead to the consumption and loss of the infundibulum as a result of holocrine sebum production. This conceptual pathogenic pathway for NICF is constructed by incorporating recent advances in the fields of follicular stem cells, wound repair, follicular homeostasis, regulatory T cells, and molecular pathways linked to the biologicals inducing NICF.